Optimization of steam utilization in palm oil refinery processes using Kaizen and design of experiment - Arif Budi Sulistyo; Fikri Fadhilah (OPSI, 2026)
This research investigates the optimization of steam consumption in the refinery process of palm oil production. Excessive steam usage during the drying stage of Spent Bleaching Earth (SBE) has resulted in higher production costs and oil content levels that do not meet company targets. To address this issue, Kaizen's continuous improvement cycle and the Design of Experiment (DOE) method were applied. Data collection involved field observation, operator interviews, and documentation, which were analyzed using Pareto diagrams and checksheets. The improvement focused on adjusting the SBE drying time as a key parameter influencing both steam usage and oil content. Prior to improvement, the drying process required 850 seconds per cycle, consuming 6,824 kg of steam per day, while producing an average oil content of 18.91%. After implementing DOE-based adjustments, the drying time was reduced to 700 seconds, decreasing steam consumption to 5,600 kg per day, a reduction of 1,224 kg/day (17.9%), and achieving an oil content of 21.03% within the company's target range of 20–22%. The study demonstrates that combining Kaizen and DOE provides an effective strategy for reducing energy usage while maintaining product quality.